Designing and Testing a Model of Some Precedents and Outcomes of Borderline Personality Disorder in High School Students of Shiraz - Seyede Fateme Sajadi; Yadolla Zargar; Mahnaz Mehrabizade Honarmand; Nasrin Arshadi (Shiraz University of Medical Sciences, 2015)
Background: Borderline Personality Disorder (BPD) characterized by emotion dysregulation, disturbed interpersonal relationship, unstable sense of self, affect and behavior, is a severe disorder with a reported suicide rate 50 times the general population. Objectives: The aim of this study was designing and testing a model for some antecedents and outcomes of borderline personality disorder. Patients and Methods: In this research child's attitude toward father and mother, early trauma, alexithymia, schema, dissociation experiences, and emotional regulation were considered as precedents of borderline personality disorder, along with associated outcomes including active addiction potential, passive addiction potential, suicide ideation and educational performance. The sample consisted of 300 high school students of Shiraz that selected via multistage random sampling. Data were collected by Borderline Personality Features Scale for Children, Early Trauma Inventory, Young's schema questionnaire-short form, Dissociative Experience Scale, Child's Attitude toward Father (CAF) and Mother (CAM) Scales, Toronto Alexithymia Scale, Difficulties in Emotion Regulation Scale (DERS), Iranian Addiction Potential Scale (IAPS), and Beck Suicide ideation Scale. Structural Equation Modeling (SEM) through AMOS 18 and SPSS 18 were used for data analysis. Results: Results suggested that model with some modification had good fit with the data. Also 2 out of 15 direct paths (the child's attitude toward father and child's attitude toward mother to emotional regulation) were not significant and thus omitted from the model. All the indirect hypotheses of model were confirmed. Conclusions: Alexithymia is correlated with all aspects of emotion dysregulation including impulsivity, negative affect, and difficulty in engaging goal-oriented behaviors and lack of skills for managing strong emotions. BPD or alexithymia patients have difficulties also in engaging cognitive reappraisal.